Management of atrial fibrillation – what is better: rate or rhythm control therapy? - Sondej, Tomasz; Czarnecka, Danuta (Przewodnik Lekarza/Guide for GPs, 2009)
Atrial fibrillation is the most common sustained arrhythmia. It may cause symptoms, heart failure and stroke. The available pharmacological interventions for AF can broadly be divided into rhythm-based and rate-based approaches, although some agents, such as amiodarone and sotalol, have therapeutic benefits for both rhythm and rate control. Early management of AF focuses on the restoration and maintenance of the sinus rhythm. Safe and effective control of atrial rhythm remains a therapeutic ideal for most patients, but rate control is especially useful in older patients with persistent or permanent AF. Recent studies have established that morbidity and mortality rates are comparable between rhythm control and rate control therapy, although the restoration of sinus rhythm is associated with both short- and long-term improvements in quality of life. Clinicians can safely use the far less invasive and usually less expensive rate-control approach in a particularly high-risk subset of AF patients for whom the best method is still an open question. Amiodarone is the most effective in prevention of AF of all class I, II and III antiarrhythmic drugs (EURIDIS, ADONIS, ATHENA). There are no differences between episodic and continuous treatment with amiodarone. Unfortunately, amiodarone causes many adverse events. A new agent, dronedarone, is thought to have the therapeutic potential to replace amiodarone. What is more, because it has no iodine group and is less lipophilic than the parent compound, dronedarone is believed to have fewer side effects and less pulmonary and thyroid toxicity.